A Domino Process for the Sustainable Synthesis of Quinazolin-4(3H)-ones with Direct Chemo- and Regioselective Bromination - Sheikhi, Ehsan; Adib, Mehdi; Yazzaf, Rozita; Jahani, Mehdi; Ghavidel, Mehdi (Synlett, 2018)
An efficient approach is reported for the direct and sustainable construction of quinazolin-4(3H)-ones through a three-component reaction of isatoic anhydride, primary amines, and bromoacetyl bromide or chloroacetyl chloride in the presence of K2CO3 in DMSO. With bromoacetyl bromide, mono- or dibrominated quinazolinone scaffolds were obtainable in a chemo- and regioselective manner.
Keywords: multicomponent reactions; quinazolinones; bromoacetyl bromide; regioselectivity; bromoquinazolines